Effect of management accounting information systems and information technology utilization on managerial performance with internal control as a moderating variable - Ammy, Baihaqi (Digital Business: Tren Bisnis Masa Depan, 2024)
The purpose of this study was to test and analyze the effect of management accounting information systems and the use of information technology on managerial performance with internal control as a moderating variable at PT. Perkebunan Nusantara IV Medan City. directly or indirectly. The approach used in this research is an associative approach. The population in this study were all employees of PT. Perkebunan Nusantara IV Medan City which numbered 323 people. The sample in this study used saturated sampling which amounted to 77 people at PT. Perkebunan Nusantara IV Medan City. Data collection techniques in this study using observation techniques, and questionnaires. The data analysis technique in this study uses a quantitative approach using statistical analysis using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Test. Data processing in this study used the PLS (Partial Least Square) software program. The results of this study prove that directly the management accounting information system has a significant effect on managerial performance. Information technology utilization has a significant effect on managerial performance. Management accounting information systems have a significant effect on managerial performance with internal control as a moderating variable. And the utilization of information technology has a significant effect on managerial performance with internal control as a moderating variable at PT. Perkebunan Nusantara IV Medan City.